Debating diversity - Takaki, Ronald (Oxford University Press, 2002)
In the nineteenth century Herman Melville wrote, "America was settled by peoples of all nations....You cannot spill a drop of American blood without spilling the blood of the whole world. We are not a narrow tribe." At the beginning of the twenty-first century, America is more ethnically diverse than ever before. Will we fear this expanding diversity as the disuniting of America, or will we embrace a more inclusive re-definition of our national identity